Multilingual and crosslingual meaning of verb prefixes - Mikelić Preradović, Nives (Array, 2013)
Multilingual dictionaries and parallel text corpora provide a powerful means for discovering the shared linguistic knowledge across languages. One of the phenomenathat has been revealed in many languages (English, Italian, Russian and especially German), but still not treated cross-linguistically, is the close relationship between the verbal aspect and Aktionsart (a syntactic-semantic category covering the manner of action, action type, verbal character or aspectual character) as well as the fact that both the aspect and Aktionsart are result of the derivational process. For the proper interpretation of Aktionsart in any language, the function of prefix in the derived verb is the mostimportant: if the prefix exhibits the function of semantic modification, then it signifies Aktionsart of the derived verb, causing the change of verbal aspect as well. In our recent research we discovered the unique semantic features of verb prefixes in Croatian and captured them in the Croatian verb valency lexicon CROVALLEX. The syntactic and semantic connection between base verbs and derived prefixed verbs was revealed and modeled as rules which contribute to the enrichment of the CROVALLEX lexicon. We analyzed all productive derivational verb prefixes in Croatian and proved that the prefix entails not only the change in the verbal aspect, but, more importantly, the change in the lexical meaning of the verb, the change in valency frame (both the number of arguments and the surface forms) as well as the syntactic-semantic class.We proved that the process of prefixation establishes connection between different base verbs that start to share the same semantic feature due to the prefix attached. Furthermore, when determining the typology of semantic features of each productive prefix in Croatian we realized that the features implicated by prefixation usually mean temporality (inchoative, punctuative, durative, iterative), locativeness, direction (adlative, ablative, perlative), dimension (intensive, diminutive), state change (resultative, mutative), transformativity, distribution, comitativity, etc. Our future step is to discover the possibility for the automatic cross-linguistic transfer of these semantic features from Croatian to Latin, Italian and German (as well as vice versa), using available digital texts of bilingual and multilingual dictionaries(digitized in the Croatian Dictionary Heritage and Croatian European Identity projector collected from free Internet sources). As a result, we plan to capture the semantic parameters of verb classes in each language that unify verbs with a certain syntactic and semantic behavior, proving the possibility to generalize the knowledge of the cross- linguistic transfer to acquire the syntax and semantics of verbs in all four languages. Research questions posed here will reveal if there is a possibility to extract the specific semantics and function of verb prefixes cross-linguistically, providing a framework for the description and comparison of individual languages. We believe that our present work sets markers for the future research, but also determine the Croatian share in the European language diversity.